IMPACT OF CHILD LABOUR ON SOCIO-ECONOMIC AND POLITICAL DEVELOPMENT IN NIGERIA - OKAFOR, Jude C; OKAFOR, Uzodinma C; NGINI, Ignatius I (Socialscientia: Journal of Social Sciences and Humanities, 2018)
The future of every state anchors so much on the youths and where the future of the child is made to suffer, it means that the future of such state is in danger. This study examined the impact of child labour on the political and social development of Nigeria. The myriad of children abuses prevalent in Nigeria is a cause to worry. The rate at which minors and under aged children suffers social diminution coming from their guardians and the society has assumed a stage of national concern. This is consequent on the societal negligence and governmental irresponsibility to rise up to his responsibilities of protecting and providing for these helpless children. It has forced the minors to embark on odd jobs against the global standard and ethics on child rights. Despite government and constitutional provisions on these children, still everything remains as if there is no future for them. This study adopted secondary source of data which was analysed using descriptive method of data analysis. It employed legal approach as its framework of analysis. The study discovers that child labour has decimated the future and hope of younger ones who found themselves trapped in the web of ruthless guardians and the law remains silent where action is needed. It resulted in a collapse on the institution assigned to enforce rules, regulations and laws made to regulate behaviours in the state and this weakness is a big threat to national development. Therefore, there should be a serious effort by the government and its various agencies trust with the responsibility of policy implementation to brace up with the challenges of commitment in the enforcement of stipulated policies to the letters.